PERAN TEKNOLOGI DALAM MENINGKATKAN KEAKTIFAN SISWA KELAS X DALAM PEMBELAJARAN AKIDAH AKHLAK DI MAN 1 PASAMAN - Yona Sefriani; Bambang Trisno; Zunaldi Zunaldi (CV. ADIBA AISHA AMIRA, 2024)
This research contains the role of technology in increasing the activity of class The aim of this research is to identify how this technology can be used in the Aqidah Akhlak learning process and what impact it will have on students' activeness in understanding and implicating moral values ​​in everyday life. The research method used in this research is a qualitative research method, where the researcher will involve interviews with PAI teachers who have utilized technology in teaching Aqidah Akhlak. The research results show that technology has played an important role in creating a more interesting and interactive learning experience for students. And the PAI teacher also mentioned that the use of technology in learning the Aqidah Moral, such as Power Point, Learning Videos, Quiz conducted online and other digital resources, is able to support students' better understanding of the concepts of the Aqidah Moral. Although many PAI teachers see the positive impact of this technology in increasing the activeness of class The implication of this research is that the use of technology in teaching Aqidah Akhlak can provide good benefits in developing students' moral skills and also requires careful planning and training to overcome challenges that may arise. This research contributes to an understanding of the role of technology in teaching the Aqidah Akhlak and provides insights that can help PAI teachers in designing more effective learning and motivating students to be more active in understanding and applying the values ​​of the Aqidah Akhlak in everyday life.